Quick Reference Guide to Citrus Insecticides and Miticides - Michael E. Rogers; Philip A. Stansly; Lukasz L. Stelinski; Jamie D. Burrow (EDIS)
This document is a two-page quick reference guide to citrus insecticides and miticides recommended in the Florida Citrus Pest Management Guide, their effects on important citrus pests, and their natural enemies. Written by M.E. Rogers, P.A. Stansly, L.L. Stelinski, and J.D. Yates, and published by the UF Department of Entomology and Nematology, January 2012.